Engineering and design : environmental statistics, environmental quality (U.S. Army Corps of Engineers, 2008)
This manual provides an overview of statistical methods that are applicable to the various life cycles of a typical environmental project.
Keywords: United States. -- Army. -- Corps of Engineers -- Handbooks, manuals, etc.; United States. -- Army. -- Corps of Engineers; Hazardous waste site remediation.; elektronické knihy; electronic books